Niat Menggunakan Big Data Analytics pada Auditor Eksternal di KAP Kota Semarang - Kharisma Syifa Auliya; Atta Putra Harjanto (Jurnal Akuntansi Bisnis, 2026)
Big Data Analytics (BDA) is a technology with significant potential to improve audit quality; however, its adoption among Audit Firms (AFs) in Indonesia remains relatively low, with only about 34% having implemented it. This study aims to analyze the factors influencing auditors’ intention to use BDA by using Technology Acceptance Model (TAM) and examining the mediating roles of perceived ease of use and perceived usefulness, which have often been overlooked in prior studies. The sample was obtained using a convenience sampling survey of external auditors working at AFs in Semarang, resulting in 124 questionnaires. The results show that training affects both perceived ease of use and perceived usefulness, while technostress only affects perceived ease of use. Furthermore, perceived usefulness significantly influences auditors’ intention to use BDA, whereas perceived ease of use does not have a significant effect. Mediation analysis indicates that perceived usefulness mediates the effect of training on the intention to use BDA. These findings provide practical implications for AFs to increase auditors’ intention to adopt BDA by investing in training and managing technostress to support optimal technology adoption.